Evaluation of the Illegal Cigarette Raid Campaign Message - Fuad, Sahlul (Jurnal Komunikasi, 2024)
Cigarette excise plays a vital role as a source of state revenue and as an instrument to reduce cigarette consumption and its negative impacts. However, the circulation of illegal cigarettes remains a significant challenge, eroding state revenues and threatening the sustainability of the legal cigarette industry. The Directorate General of Customs and Excise (DJBC), in collaboration with local governments, has implemented the Gempur Rokok Ilegal (GRI) campaign to combat illegal cigarettes through repressive actions and public education. This study aims to evaluate the GRI campaign messages to provide recommendations for future improvements. Using a qualitative method with a case study approach, this research involved observations, interviews, and document analysis in Demak Regency, the highest recipient of tobacco excise revenue-sharing funds (DBH CHT) in the Semarang Customs region. Data were analyzed using the Elaboration Likelihood Model (ELM) to assess the effectiveness of campaign messages. The findings reveal that face-to-face campaign messages are more comprehensive and persuasive compared to print media. Face-to-face messages integrate information about excise, the impact of illegal cigarettes, and a call to action as reporting agents. In contrast, print media tends to be informative, with monotonous designs and lacking adequate persuasive elements. Recommendations include integrating informative and emotional content in print media, using logical and emotional appeals aligned with ELM principles, and strengthening visuals to motivate behavioral change. A holistic approach is expected to enhance public awareness and participation in combating illegal cigarettes